PROCESSION OF "TEPUNG TAWAR" AS AN ALTERNATIVE SOLUTION FOR CRIMINAL CASE IN MALAY CUSTOM LAW OF RIAU - ERDIANTO ERDIANTO (Jurnal Dinamika Hukum, 2015)
Implementation of the principle of legality in criminal law enforcement Indonesia in fact has caused some problems in the case and piling them over the prison capacity. It is necessary to find a model that is based on the completion of criminal cases and restorative local wisdom . One model that is “tepung tawar” in Malay society . Through empirical legal research found that the model completion of minor criminal matters in the Malay community is not united in procession “tepuk tepung tawar” but in other models, namely the density “ninik mamak” or different with “tepung tawar” practices applied in Jambi and South Sumatra , but the settlement of disputes and several criminal cases in the Malay community is also done with a model of restorative approaches .Keywords : Tepung Tawar, criminal case , Melayu, restoratife justice